Position Group Contribution Method for Predicting the Normal Boiling Point of Organic Compounds - 王强 马沛生 王昶 夏淑倩 (Chinese journal of chemical engineering, 2009)
A new position group contribution model is proposed for the estimation of normal boiling data of organic compounds involving a carbon chain from C2 to C18. The characteristic of this method is the use of position distribution function. It could distinguish most of isomers that include cis- or trans-structure from organic com- pounds. Contributions for hydrocarbons and hydrocarbon derivatives containing oxygen, nitrogen, chlorine, bro- mine and sulfur, are given. Compared with the predictions, results made use of the most common existing group contribution methods, the overall average absolute difference of boiling point predictions of 417 organic com- pounds is 4.2 K; and the average absolute percent derivation is 1.0%, which is compared with 12.3 K and 3.2% with the method of Joback, 12.1 K and 3.1% with the method of Constantinou-Gani. This new position contribution groups method is not only much more accurate but also has the advantages of simplicity and stability.